Comics and the Body Drawing, Reading, and Vulnerability - Szép, Eszter (The Ohio State University Press, 2020)
Eszter Szép's Comics and the Body is the first book to examine the roles of the body in both drawing and reading comics within a single framework. With an explicit emphasis on the ethical dimensions of bodily vulnerability, Szép takes her place at the forefront of scholars examining comics as embodied experiences, pushing this line of inquiry into bold new territory. Focusing on graphic autobiography and reportage, she argues that the bodily performances of creators and readers produce a dialogue that requires both parties to experience and engage with vulnerability, thus presenting a crucial opportunity for ethical encounters between artist and reader. Szép considers visceral representations of bulimia, pregnancy, the effects of STIs, the catastrophic injuries of war, and more in the works of Lynda Barry, Ken Dahl, Katie Green, Miriam Katin, and Joe Sacco. She thus extends comics theory into ethical and psychological territory that finds powerful intersections and resonances with the studies of affect, trauma, gender, and reader response.